High Crystallization of Perovskite Film by a Fast Electric Current Annealing Process - Luo, Wei; Wu, Cuncun; Sun, Weihai; Guo, Xuan; Xiao, Lixin; Chen, Zhijian (ACS APPLIED MATERIALS & INTERFACES, 2017)
High-efficiency organic inorganic hybrid perovskite solar cells have experienced rapid development and attracted significant attention in recent years. Crystal growth as an important factor would significantly influence the quality of perovskite films and ultimately the device performance, which usually requires thermal annealing for 10 min or more. Herein, we demonstrate a new method to get high crystallization of perovskite film by electric current annealing for just 5 s. In contrast to conventional thermal annealing, a homogeneous perovskite film was formed with larger grains and fewer pinholes, leading to a better performance of the device with higher open-circtlit voltage and fill factor. An average power conversion efficiency of 17.02% with electric current annealing was obtained, which is higher than that of devices with a conventional thermal annealing process (16.05%). This facile electric current annealing process with legs energy loss and time consumption shows great potential in the industrial mass production of photovoltaic devices.